Development and characterization of dialdehyde xanthan gum crosslinked gelatin based edible films incorporated with amino-functionalized montmorillonite. (October 2015) - Ge, Liming; Li, Xinying; Zhang, Run; Yang, Tianhan; Ye, Xiaowei; Li, Defu; Mu, Changdao
Abstract: The amino-functionalized montmorillonite (NH2 -MMT) with different amino content is successfully prepared by adjusting the solvents proportion of anhydrous ethanol and toluene. Then NH2 -MMT is incorporated into gelatin to prepare composite edible films using dialdehyde xanthan gum (DXG) as the crosslinking agent. The XRD studies indicate that the amino-functionalization is beneficial for MMT to disperse and exfoliate in gelatin matrix and the incorporation of NH2 -MMT can induce gelatin molecules to renature into triple-helix structure. The amino-functionalization of MMT provides active sites for the crosslinking by Schiff's base reaction to produce compact networks among gelatin, NH2 -MMT and DXG. Moreover, the increase of amino content of NH2 -MMT consequentially improves the crosslinking density of the composite films. Hence, the UV light barrier property, water resistance, mechanical property and thermal stability of the composite films are improved with the addition of NH2 -MMT and increase along with the increase of amino content of NH2 -MMT. The study demonstrates that NH2 -MMT is an ideal filler for gelatin based composite edible films. Graphical abstract: Highlights: The amino-functionalized montmorillonite was successfully incorporated into gelatin. The amino-functionalization was beneficial for montmorillonite to disperse in gelatin. The amino-functionalized montmorillonite could induce gelatin molecules to renature. The amino-functionalized montmorillonite could improve the properties of gelatin films. The amino-functionalized montmorillonite was an ideal filler for gelatin films.